Selçuk Type Headgear-Tımer (Stht) (The Presentatıon And Testıng Its Accuracy) Part: I A Laboratory Study - Enis Güray; Metin Orhan (Galenos Yayinevi, 1994)
In the present study "Selçuk Type Headgear-Timer" (STHT) was described and tested on laboratory conditions. 10 STHT's were compared with real time measurements for 4 months. Its accuracy was found 100% in minute. STHT is also independent of force variable, resistant, easy to constuct and cheap.